Revisiting the concept of Economic Development and the School of Thought of Developmentalism in Economics - DE MORAES, Isaías Albertin [UNESP] (FapUNIFESP (SciELO), 2023)
This paper aims to revisit and systematize the concepts of Economic Development and Developmentalism. The hypothesis raised by the research is that due to the historical-social procedurality of Economic Sciences, the terms Economic Development and Developmentalism can be categorized differently by epistemological and didactic option nowadays. The article opted to perform a bibliographic study. The methodological procedures for selecting the references were bibliographic research focused on the authors with historical, concrete and inductive analysis of the economy and the phenomenon of economic development. The results obtained are that the terms Economic Development and Developmentalism can be categorized differently, one as a concept used by several schools of economic thought; other as a School of Economic Thought, which has four theoretical currents (Classical Developmentalism, Social Developmentalism, New Developmentalism, Socialist Market Developmentalism).
Revisitando o conceito de Desenvolvimento Econômico e a Escola de Pensamento do Desenvolvimentismo na Economia
Keywords: developmentalism; Economic development; economic theory; history of economic thought